Current Account and Saving Account Determinants of Indonesian Banks - Murharsito Murharsito; Fitri Ella Fauziah (Universitas Nusantara PGRI Kediri, 2026)
The mobilization of deposits, particularly CASA, plays a strategic role as it represents a low-cost funding source that can reduce interest expenses while simultaneously enhancing bank profitability. This study aims to examine the factors influencing CASA fund mobilization in the banking sector, with suspected influencing variables including CAR, bank size, BOPO, and NPL. The analysis employs a panel data regression method utilizing annual financial report data from 43 banking issuers listed on the Indonesia Stock Exchange (IDX) over the period 2013–2024, yielding a total of 486 observations. Based on estimations using the fixed effect model, the results reveal that only the non-performing loan (NPL) ratio is proven to be a significant determinant with a negative impact on the CASA ratio. Meanwhile, CAR, bank size, and operational efficiency (BOPO) do not exhibit significant influence. These findings provide important implications that risk perception and customer confidence, as reflected by bank asset quality, are key factors in mobilizing low-cost funds, thereby necessitating that prudent credit risk management be prioritized.